Storage stability of traditional Tunisian butter enriched with antioxidant extract from tomato processing by-products. (15th October 2017) - Abid, Yousra; Azabou, Samia; Jridi, Mourad; Khemakhem, Ibtihel; Bouaziz, Mohamed; Attia, Hamadi
Highlights: The effect of incorporating TPBE, rich in antioxidants, in TTB was evaluated during storage. The addition of low dose of TPBE ameliorates the texture and oxidative stability. The addition of high concentration of TPBE may act as a pro-oxidant. The natural antioxidants in the TPBE added to TTB can be as effective as BHA. Abstract: Traditional Tunisian butter (TTB) is one of the most appreciated dairy products in Tunisia. Herein, the storage stability of TTB enriched with antioxidants from tomato processing by-products (TPB) was evaluated during 60 days of storage at 4 °C. TPB extract contains significant amounts of lycopene and phenolics. TTB enriched with 400 mg of TPB extract/kg of TTB revealed the lowest peroxide values at all the determination intervals. Adding 400 mg of TPB extract/kg of TTB did not exhibit any undesired effect on lactic bacteria which are necessary for development of aroma and chemical properties of TTB. However, raw TTB and highly enriched TTB (800 mg of TPB extract/kg of TTB) displayed higher lipid peroxidation. The detrimental effect of high antioxidant amounts on TTB stability could be due to a possible pro-oxidant character. Thus, appropriate supplementation of TPB extract could be used in TTB as a protective agent against lipid peroxidation to extend its shelf-life up to two months.